2008
DOI: 10.1111/j.1365-2141.2008.07216.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired pure red cell aplasia: updated review of treatment

Abstract: Pure red cell aplasia (PRCA) is a syndrome characterized by a severe normocytic anaemia, reticulocytopenia, and absence of erythroblasts from an otherwise normal bone marrow. Primary PRCA, or secondary PRCA which has not responded to treatment of the underlying disease, is treated as an immunologically-mediated disease. Although vigorous immunosuppressive treatments induce and maintain remissions in a majority of patients, they carry an increased risk of serious complications. Corticosteroids were used in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
191
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 196 publications
(197 citation statements)
references
References 88 publications
1
191
1
4
Order By: Relevance
“…Thereafter, treatment with cyclosporine at a trough level of at least 150 ng/mL is necessary for maintaining remission [23]. In our case, the patient was taking omeprazole at the start of cyclosporine, and it is reported that omeprazole reduces the hepatic clearance of cyclosporine by inhibition of cytochrome P450 enzyme system, thus leading to higher cyclosporine levels with the same dosage [24].…”
Section: Discussionmentioning
confidence: 78%
“…Thereafter, treatment with cyclosporine at a trough level of at least 150 ng/mL is necessary for maintaining remission [23]. In our case, the patient was taking omeprazole at the start of cyclosporine, and it is reported that omeprazole reduces the hepatic clearance of cyclosporine by inhibition of cytochrome P450 enzyme system, thus leading to higher cyclosporine levels with the same dosage [24].…”
Section: Discussionmentioning
confidence: 78%
“…[9] PRCA secondary to parvovirus B19 can be treated with intravenous immunoglobulin. [10] Corticosteroids (CS) were the first immunosuppressive drugs used in the treatment of PRCA and so far have been considered the treatment of first choice, especially in young adults. [9] In our patient oral steroid therapy was successful and showed improvement as evidenced by rise in haemoglobin to almost normal range in 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…En una revisión reciente 12 referente a tratamiento, se describen varias alternativas, entre ellas corticoides, ciclosporina y ciclofosfamida, y globulina antitimocito. La respuesta al tratamiento inmunosupresor en nuestro caso con corticoides y ciclosporina fue efectivo y rápido, con normalización del nivel de hemoglobina al mes de tratamiento.…”
Section: Discussionunclassified